Cloning, purification and characterization of a novel GH46 family chitosanase, Csn-CAP, from Staphylococcus capitis. (December 2018) - Sun, Huihui; Cao, Rong; Li, Laihao; Zhao, Ling; Liu, Qi
Graphical abstract: Highlights: A novel cold-adapted chitosanase Csn-CAP from Staphylococcus capitis was identified. Csn-CAP is a novel member of GH46 family. Csn-CAP exhibits an endo-type cleavage pattern. Csn-CAP hydrolyzes chitosan to yield mainly (GlcN)2 and (GlcN)3 . Abstract: A novel chitosanase gene, designated csn-cap, was cloned from Staphylococcus capitis with codon optimization and functionally expressed in Escherichia coli M15. The recombinant enzyme Csn-CAP, which belongs to the GH46 family, consists of 342 amino acids, which includes a 35-amino acid signal peptide. The mature protein was purified to homogeneity using Ni-NTA affinity chromatography, and the molecular mass of the purified enzyme was estimated to be ∼35 kDa by SDS-PAGE. Csn-CAP displayed a maximal activity at 30 °C and pH 7 and a weak alkaline solution could inhibit its activity harshly. The enzyme was cold-adapted and exhibited 86% of its maximal activity at 20 °C. The level of enzymatic activity was enhanced by some bivalent metal cations, such as Zn 2+, Cu 2+ and especially Mn 2+, which could enhance the activity more than twofold at a 5 mM concentration. The enzyme exhibited strict substrate specificity for chitosan solution, colloidal chitosan and powdery chitosan, but it could not hydrolyze colloidal chitin or carboxymethylcellulose. The thin-layer chromatography result showed that Csn-CAP exhibited an endo-type cleavage pattern and hydrolyzed chitosan to yield mainly (GlcN)2 and (GlcN)3 . Thus, the novel characteristics of the chitosanase Csn-CAP make it a potential candidate for oligosaccharide production-based industries.